1996
DOI: 10.1007/bf03025952
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature plastic flow behaviour in the binder of WC-Co cemented carbides

Abstract: Co-rich solid solution alloys regarded as the composition of binder phasesat elevated temperatures in WCCo cemented carbides were fabricated and the high-temperature deformation behaviour of the alloys was investigated. The logarithmic relationship between flow stress and strain rate is expressed by a single straight line with the slope of t).15 at a constant temperature in all strain rate range examined, unlike in cemented carbides showing the sigmoidal behaviour. The solid solution hardening due to the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Chung (1956Chung ( , 1965 illustrated 11 species, and Kitagawa (1979) recorded 13 species, one variety, and one forma in Korean Allium. Lee (1996) summerized Korean Allium as 17 species, three varities, and two formas including cultivars. Yu et al (1981) studied the taxonomy of the Korean Allium, and reported 12 species, two varieties, and one forma.…”
mentioning
confidence: 99%
“…Chung (1956Chung ( , 1965 illustrated 11 species, and Kitagawa (1979) recorded 13 species, one variety, and one forma in Korean Allium. Lee (1996) summerized Korean Allium as 17 species, three varities, and two formas including cultivars. Yu et al (1981) studied the taxonomy of the Korean Allium, and reported 12 species, two varieties, and one forma.…”
mentioning
confidence: 99%